Unintended effects of herbicide exposure on non-target beetle Zygogramma bicolorata Pallister, 1953, a bio-control agent of Parthenium hysterophorus weed - Neha Singh; Nikhil Maheshwari; Ayesha Qamar (Journal of Basic and Applied Zoology)
Abstract Background Herbicides are commonly used to safeguard crops against weed damage, but their effects on non-target organisms like Zygogramma bicolorata, a natural bio-control agent feeding on Parthenium hysterophorus, an invasive weed, have raised concerns. This study investigates the impact of pendimethalin, a widely used herbicide, on Z. bicolorata. Results The results of the present study reveal adverse effects induced by pendimethalin on various life parameters of Z. bicolorata. Fecundity decreased by approximately 20.98%, while egg viability reduced by about 18.36%. Female lifespan decreased by approximately 11.18%, and male lifespan decreased by about 13.80%, with an associated increase in developmental time period. Oviposition days after pendimethalin treatment showed only a minor 9.18% decrease compared to the control group. Pendimethalin also negatively impacted the gut antioxidants of Z. bicolorata, resulting in oxidative stress that can harm gut health and disrupt biological processes. At the molecular level, it has also been observed the DNA damage in the midgut tissue of Z. bicolorata. Conclusion This study underscores the unintended consequences of herbicide use on non-target organisms, emphasizing the potential threats to biodiversity. Evaluating chemical impacts on non-target organisms is crucial for ensuring responsible and sustainable chemical use in agriculture and other sectors.